Postpartum Acquired Hemophilia: A Rare Cause of Postpartum Hemorrhage - Srikanth Seethala; Sumit Gaur; Elizabeth Enderton; Javier Corral (Case Reports in Hematology)
A 36-year-old female started having postpartum vaginal bleeding after normal vaginal delivery. She underwent hysterectomy for persistent bleeding and was referred to our institution. An elevation of PTT and normal PT made us suspect postpartum acquired hemophilia (PAH), and it was confirmed by low factor VIII activity levels and an elevated factor VIII inhibitor. Hemostasis was achieved with recombinant factor VII concentrates and desmopressin, and factor eradication was achieved with cytoxan, methylprednisolone, and plasmapheresis.